Effect of mixing period, water and sugar on the sesame cracker dough stickiness - Tan, S. B.; Shamsudin, Rosnah; Mohammed, M. A.; Rahman, N. A. (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2016)
Sesame Cracker or Kuih Bijan is a popular traditional Malays snack in Malaysia. The simplest formulation of Sesame Cracker dough includes glutinous rice flour, sugar, and water. In order to reduce the negative effect caused by dough stickiness, the effect of mixing period (3 to 7 minutes), water (41.6 to 45.6%) and sugar (1 to 9%) on dough stickiness of sesame cracker dough were studied using Texture Analyzer and Chen-Hoseney methodologies (i.e. Chen-Hoseney Dough Stickiness Cell). The result obtained showing that the increment of mixing time, water and sugar addition, increased the dough stickiness, work of adhesion/adhesiveness and dough strength/cohesiveness. However, overmixing of dough had led to the decrease of these parameters.